The Relationship Between Fetuin-A and Bone Mineral Density in Postmenopausal Osteoporosis - Aylin SARI,; Turan USLU2, (Archives of Rheumatology, 2013)
Objectives: This study aims to evaluate the relationship between fetuin-A and bone mineral density (BMD) in postmenopausal women. Patients and methods: Between November 2009 and March 2010, 90 participants were enrolled in the study and divided into three groups including 30 patients in each group. Group 1 consisted of patients who were newly diagnosed with postmenopausal osteoporosis, group 2 consisted of patients who were previously diagnosed with postmenopausal osteoporosis and received treatment, and the control group consisted of healthy volunteers with normal postmenopausal BMD values. Serum fetuin-A level was measured using an enzyme-linked immunosorbent assay (ELISA). Anteriorposterior (AP) lumbar spine, femur neck and total femur BMD were evaluated using dual energy X-ray absorptiometry. Results: A statistically significant relationship was observed between serum fetuin-A levels and BMD scores. As AP lumbar spine, femur neck and total femur BMD values the fetuin-A levels became lower, serum fetuin-A level decreased. Serum fetuin-A level was lower in patients with postmenopausal osteoporosis, compared to the control group. Serum fetuin-A was not affected by osteoporosis treatment in these patients. Conclusion: Our study results confirm that BMD parameters are associated with fetuin-A and therefore postmenopausal osteoporosis and fetuin-A. Fetuin-A, a marker for bone mineralization, can be used as a biomarker in the diagnosis and treatment of postmenopausal osteoporosis.